Pemenuhan Royalti dan Perlindungan Hukum Hak Cipta Lagu yang Diplagiat di YouTube - Tua, Raja Marsaringar Mangappu Tua; Wetmen Sinaga; Haposan Sahala Raja Sinaga (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
After a creation is realized in a tangible form without reducing restrictions in accordance with statutory provisions, copyright is the exclusive right of the creator that automatically arises based on the declarative principle. As the creator’s economic rights, they are entitled to compensation in the form of royalties. LMKN handles the distribution, collection, and withdrawal of royalties. This study employs normative legal research, which is backed up by empirical research. The statutory approach is the one that is taken. This study draws on primary, secondary, and tertiary legal sources for its legal sources. Interviews and library techniques are utilized for data collection. In order to safeguard copyrighted songs and music, legislation such as Law No. 28 of 2014, Law No. 19 of 2002, and Government Regulation No. 56 of 2021 pertaining to the Management of Song and/or Music Copyright Royalties were enacted.